Perceptions and experiences of Hospital-Acquired Diarrhea among children aged 0–59 months with Severe Acute Malnutrition at Mwanamugimu Nutrition Unit, Mulago, Uganda: A qualitative study - Mahad Muweesi; Agnes Nyabigambo; Arthur Bagonza; Musaazi John Francis Kimuli; Grace Rickson Nsubuga; Christopher Garimoi Orach (PLoS ONE, 2026)
Background Hospital-Acquired Diarrhea (HAD) is a global health threat and a leading cause of illness and death in children with Severe Acute Malnutrition (SAM). In Uganda, HAD significantly affects children under five with SAM, creating a heavy health and economic burden. This study explored caregivers’ and health workers’ perceptions and experiences of HAD among children aged (0–59) months with SAM regarding HAD at Mwanamugimu Nutrition Unit, Mulago, Uganda. Methods A qualitative study was conducted at Mwanamugimu Nutrition Unit, involving 12 caregivers and 10 health workers. Audio-recorded data were collected through in-depth interviews (IDIs) and key informant interviews (KIIs). Data was managed using Atlas ti version 6 and thematically analyzed to identify perceptions and experiences of HAD among children (0–59) months with SAM at Mwanamugimu. Results The results are presented according to the major themes that emerged from the data: understanding health risk of HAD and their impact, advantages and challenges of health interventions, empowerment through health education, prompts and motivators for action. Caregivers reported emotional distress, inadequate communication with patient progress by health workers, limited family social support, difficulty in maintaining clean toilets, and financial constraints for diapers and other sanitary items as contributors to HAD. Health workers attributed HAD to inconsistent water supply, inadequate dietary knowledge, and poor infection control. Both groups stressed that motivational triggers are essential for sustainable adherence to management guidelines. Conclusion This study emphasizes the urgent need to empower caregivers through targeted health education, adequate hygiene support, and structured ward routines. Strengthening caregiver confidence and participation enhances adherence and recovery among children with severe acute malnutrition. Integrating psychosocial support and participatory strategies into hospital nutrition programs can reduce hospital-acquired diarrhea and promote sustainable, high-quality child health outcomes.